Prevalence and gender association of radix entomolaris in mandibular molars - RASIDI, MOHAMAD QULAM ZAKI BIN MOHAMAD; S, DEEPAK.; PRABU, DINESH (The journal of contemporary issues in business and government, 2021)
Endodontic treatment with excellent outcomes depends on the critical identification of the root and its canals anatomy. The successful identification of these anatomies guaranteed the pulp tissue extirpation completely, with efficiency in chemo-mechanical cleaning and shaping. All these lead to three-dimensional root canal obturation with the most reliable inert filling. Therefore, the aim of this study was to evaluate the occurrence of radix entomolaris in mandibular molars between male and female patients. A total of 1503 patient records were reviewed and analyzed from June 2019 to March 2020 in Saveetha Dental College. All 1503 patients were assessed for the radix entomolaris, data entered in Microsoft excel sheet, and transferred to SPSS software for statistical results. The Chi-Square test was done to analyze the correlation between the gender prevalence of radix entomolaris in mandibular first molars. The prevalence of patients with Radix Entomolaris was 0.5% (7 of 1503), 0.47% (4 of 843) for females, and 0.45% (3 of 660) for males, which showed statistically insignificant (p-value >0.05). Within the limitations of the study, there is no significant evidence suggesting that gender plays a major role in the occurrence of Radix Entomolaris.